2020
DOI: 10.5114/jcb.2020.96863
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-125 seed implantation for residual hepatocellular carcinoma or cholangiocellular carcinoma in challenging locations after transcatheter arterial chemoembolization. Initial experience and findings

Abstract: Purpose To evaluate the clinical efficacy and safety of computed tomography (CT)-guided iodine-125 ( 125 I) seed implantation (ISI) for hepatocellular carcinoma (HCC) or cholangiocellular carcinoma (CCC) lesions in challenging locations after transcatheter arterial chemoembolization (TACE). Material and methods A retrospective single-center review of 24 patients with HCC or CCC tumors in challenging locations (hepatic dome or close to the hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Hence, 125 I seeds may facilitate superior therapeutic efficacy for TACE treatment. RSI can also efficiently treat residual HCC tumor cells following TACE [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, 125 I seeds may facilitate superior therapeutic efficacy for TACE treatment. RSI can also efficiently treat residual HCC tumor cells following TACE [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For one, tumor embolization can restrict the tumor blood flow [ 21 ]. In addition, TACE can generate high levels of ischemia and inflammatory edema in the peritumoral regions, contributing to greater brachytherapeutic benefits upon 125 I seed insertion [ 10 , 11 ]. The 125 I seeds were also able to destroy hypovascular HCC tumor regions refractory to precision TACE treatment [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate imaging assessment after ablation and closer follow-up monitoring are necessary for patients with periportal HCC to prevent rapid tumor progression due to residual tumor or tumor recurrence. In addition, non-RFA-related technologies could provide an alternative option for periportal HCC to prevent or minimize newly recognized RFA-related tumor recurrence [ 20 ], such as microwave ablation [ 25 ], cryoablation [ 26 ] and irreversible electroporation [ 27 ], and iodine-125 seed implantation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some reports suggested that sorafenib was less effective in those with Vp3/4 PVTT (< 10% of response rate) [ 6 , 9 ]. In contrast, 125 I seed implantation in the portal vein allowed for effective PVTT control owing to sustained low-dose X- and γ-ray release throughout the tumor area, damaging tumor cell DNA and disrupting proliferation [ 11 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%